1984
DOI: 10.1111/j.1442-9993.1984.tb01369.x
|View full text |Cite
|
Sign up to set email alerts
|

The impact of water buffalo on the monsoon forest ecosystem in Kakadu National Park

Abstract: The intensity of use of forested country in the Kakadu National Park area b\ feral Asiatic water buffalo can be largely predicted from the area of river floodplain in the vicinity of the site, and tree canopy cover on the site. Thus some areas of monsoon forest appear to have sustained intensive use by buffalo for over a century whereas other areas have probably been little used.With sites exhibiting little buffalo use, mean DBH of trees increased with foliage height diversity (FHD). However, the sites more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 19 publications
3
28
1
Order By: Relevance
“…In lowland habitat types, Russell-Smith (1984) found that the most obvious impact was the elimination of the lower strata of woody plants as well as the death of canopy trees. This is consistent with the impacts recorded by Braithwaite et al (1984), who sampled 30 monsoon rain forest patches in KNP and compared sites with varying intensity of use by buffalo. They concluded that buffalo had a fundamental impact on vegetation structure and composition, including reduced lower canopy cover, and postulated that soil compaction by buffalo caused the death of large trees by hindering groundwater recharge.…”
Section: Monsoon Rain Forestssupporting
confidence: 89%
See 2 more Smart Citations
“…In lowland habitat types, Russell-Smith (1984) found that the most obvious impact was the elimination of the lower strata of woody plants as well as the death of canopy trees. This is consistent with the impacts recorded by Braithwaite et al (1984), who sampled 30 monsoon rain forest patches in KNP and compared sites with varying intensity of use by buffalo. They concluded that buffalo had a fundamental impact on vegetation structure and composition, including reduced lower canopy cover, and postulated that soil compaction by buffalo caused the death of large trees by hindering groundwater recharge.…”
Section: Monsoon Rain Forestssupporting
confidence: 89%
“…Although research on the mechanisms of buffalo impacts on monsoon rain forests is sparse, within the patches of monsoon rain forest themselves most of the impact appears to be due to the direct effects of buffalo activity: soil and root compaction, browsing, wallowing and physical destruction of vegetation (Braithwaite et al 1984, Russell-Smith and Dunlop 1987, Russell-Smith and Bowman 1992 Table 1). Russell-Smith (1984) showed that in sandstone terrain, only those rain forest sites associated with springs or streamline habitats were seriously affected by buffalo, while in the lowlands, impact was widespread.…”
Section: Monsoon Rain Forestsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ehmann (1992) considered that trampling and denudation of vegetation by cattle may be contributing to decline in Ophidiocephalus. Friend and Cellier (1990) illustrated decline in some herpetofauna species associated with high densities of feral Water Buffalo Bubalus bubalis, and Braithwaite et al (1984) also found associations, both positive and negative, between different herpetofauna species and buffalo impacts. Both of these studies were correlative; there has been no long-term research or use of exclosure plots.…”
Section: Conservation and Managementmentioning
confidence: 98%
“…However, given that there were no sustained density-reduction programmes in place after the initial culls, populations of buffalo rebounded strongly and now number around 150,000 animals ). At higher densities, swamp buffalo cause major environmental damage such as saltwater intrusion into sensitive wetlands through the trampling of sensitive vegetation and browsing on remnant monsoon forest during the harsh late dry season when native pasture quantity and quality is declining (Bowman et al 2008;Braithwaite et al 1984;Petty et al 2007;Werner 2005;Werner et al 2006). Economically, buffalo are a major threat to Australia's livestock industry as hosts and vectors for diseases such as foot-and-mouth (Cousins and Roberts 2001;Ward et al 2007), and their broad dietary niche allows them to compete with cattle for pasture during the dry season (Bowman et al 2010).…”
Section: Introductionmentioning
confidence: 99%